Assessment of microfungal contamination and enzymatic activity in ethnographic textile artifacts and museum environment - Guven Ozdemir; Alev Haliki; Melike Çelebi (PLoS ONE, 2026)
Ethnographic textile artifacts are highly susceptible to fungal biodeterioration due to their organic composition and continuous exposure to microfungi in museum environments. This study aimed to assess the extent of microfungal contamination in the exhibition and storage areas of the Ege University Ethnography Museum and to evaluate the enzymatic activities (cellulase and protease) of the isolated fungal species to determine their biodeterioration potential. Air and surface samples were collected from display halls, storage rooms, and outdoor reference points during two seasons (spring and autumn) using a portable air sampler on DG-18, PCA, and MEA media. Fungal isolates were identified through macroscopic and microscopic examination supported by standard mycological keys, and their enzymatic activity was assessed using CMC agar for cellulase and skim milk agar for protease production. Microclimatic influences and seasonal differences were statistically evaluated using a two-sample independent t-test. Fungal load ranged from 120–450 CFU/m³ on DG-18 and 300–1000 CFU/m³ on PCA, with the highest values recorded inside display cases and storage zones. A total of 58 fungal isolates were obtained, predominantly belonging to Aspergillus, Penicillium , Cladosporium, Alternaria , and Rhizopus . Enzymatic assays showed that several isolates exhibited strong cellulase and protease activities, particularly A. sydowii, P. citrinum, A. flavus , and P. chrysogenum , indicating a high biodeterioration risk for cellulose- and protein-based textiles. Seasonal differences were statistically insignificant, highlighting the greater importance of microclimatic conditions and ventilation patterns. These findings underscore the need for integrated biological risk management and continuous microbial monitoring to protect ethnographic textile heritage from fungal deterioration.